PENGARUH BERBAGAI MACAM DAN DOSIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAGODA (Brassica narinosa L) - faizal arba'i sidiq; Anis Rosyidah; Siti Muslikah (AGRONISMA, 2021)
Pagoda mustard plant (Brassica narinosa L.) is a plant of the brassicaceae family that has a beautiful shape. In increasing the growth and yield of organic pesticide-free mustard greens, one of them is by providing liquid organic fertilizer. Liquid Organic Fertilizer (LOF) of golden snail meat which contains nitrogen and banana weevil which contais phosphate are organic materials that can be used for organic liquid fertilizer needed by vegetable plants. The purpose of giving liquid organic fertilizer in this research was to determine the effect of growth and yield of pagoda mustard plants, to find out the best results between the two types of liquid organic fertilizers and to obtain the optimal dose obtained at the dose of the two liquid organic fertilizer. The design used in this research was a 2 factorial Randomized Block Design (RBD). The first factor is the type of LOF material (Golden snail meat and banana weevil), the second factor is the dose of LOF given (50ml/polybag, 100ml/polybag, 150ml/polybag and 200ml/polybag). The result of reseacrh on the growth of the pagoda mustard plant showed that the combination of P1D4 (Golden Snail Liquid Fertilizer 200ml) gave the best result at the 28 dap in the number leaves obtained. On harvesting the pagoda mustard plants separately, the LOF at D4 (200ml/polybag) had a significant difference with the others. Between the application of Liquid Organic Fertilizer (LOF) gold snail and banan weevil did not show a significant difference between the two ingredients.